2021
DOI: 10.1177/08850666211001799
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Features and Risk Factors for In-Hospital Mortality From COVID-19 Infection at a Tertiary Care Medical Center, at the Onset of the US COVID-19 Pandemic

Abstract: Background: Mortality from COVID-19 has been associated with older age, black race, and comorbidities including obesity, Understanding the clinical risk factors and laboratory biomarkers associated with severe and fatal COVID-19 will allow early interventions to help mitigate adverse outcomes. Our study identified risk factors for in-hospital mortality among patients with COVID-19 infection at a tertiary care center, in Detroit, Michigan. Methods: We conducted a single-center, retrospective cohort study at a 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
1
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 33 publications
1
24
1
2
Order By: Relevance
“…The less common symptoms were myalgia, sore throat, headache, fatigue, rhinitis, loose stools, vomiting, and anosmia. More patients reported complaints of breathlessness along with fever and cough, compared to other studies [19,20]. The probable reason could be that ours being a referral center, many patients might have been admitted days after the onset of disease.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…The less common symptoms were myalgia, sore throat, headache, fatigue, rhinitis, loose stools, vomiting, and anosmia. More patients reported complaints of breathlessness along with fever and cough, compared to other studies [19,20]. The probable reason could be that ours being a referral center, many patients might have been admitted days after the onset of disease.…”
Section: Discussionmentioning
confidence: 73%
“…This is in line with the higher in-hospital case fatality rate in referral tertiary care centers compared to the general population. A tertiary care medical center in the USA, which also had a high proportion of patients with comorbidities (95.2%), reported a case fatality rate of 30% during the early phase of the pandemic [19].…”
Section: Discussionmentioning
confidence: 99%
“…After a preliminary review and the elimination of duplicates, 5328 papers were screened and chosen for further evaluation. A total of 58 studies (Adejumo et al 2021 ; Akhtar et al 2021 ; Alpert et al 2021 ; Arslan et al 2021 ; Azarkar et al 2021 ; Baker et al 2021 ; Benelli et al 2020 ; Bennett et al 2021 ; Bergman et al 2021 ; Bernard et al 2021 ; Bhargava et al 2021 ; Borobia et al 2020 ; Pinto et al 2020 ; Chai et al 2021 ; Fu et al 2021 ; Chudasama et al 2021 ; Costa et al 2021 ; Duanmu et al 2020 ; Gold et al 2020 ; Görgülü et al 2020 ; Goyal et al 2020 ; Gude-Sampedro et al 2021 ; Guo et al 2021 ; Joharatnam-Hogan et al 2020 ; Katkat et al 2021 ; Kim et al 2021 ; Kokturk et al 2021 ; Liang et al 2021 ; Sun et al 2021 ; Cavanna et al 2020 ; Lunski et al 2021 ; Martinot et al 2021 ; Mirgh et al 2021 ; Miyashita et al 2020 ; Nakamura et al 2021 ; Nikpouraghdam et al 2020 ; Panda et al 2022 ; Péron et al 2021 ; Poli et al 2022 ; Li et al 2020a , b ; Reddy et al 2021 ; Regina et al 2020 ; Ricoca-Peixoto et al 2020 ; Giorgi-Rossi et al 2020 ; Rugge et al 2020 ; Erdal et al 2021 ; Sami et al 2020 ; Santorelli et al 2021 ; Pérez-Segura et al 2021 ; Serraino et al 2021 ; Shahidsales et al 2021 ; Sorouri et al 2020 ; Stroppa et al 2020 ; Tehrani et al 2021 ; Vergara et al 2021 ; Vila-Corcoles et al 20...…”
Section: Resultsunclassified
“…A total of 42 studies (Akhtar et al 2021 ; Alpert et al 2021 ; Arslan et al 2021 ; Azarkar et al 2021 ; Baker et al 2021 ; Benelli et al 2020 ; Bennett et al 2021 ; Bernard et al 2021 ; Bhargava et al 2021 ; Borobia et al 2020 ; Pinto et al 2020 ; Chai et al 2021 ; Fu et al 2021 ; Gude-Sampedro et al 2021 ; Guo et al 2021 ; Joharatnam-Hogan et al 2020 ; Katkat et al 2021 ; Kim et al 2021 ; Kokturk et al 2021 ; Liang et al 2021 ; Sun et al 2021 ; Lunski et al 2021 ; Martinot et al 2021 ; Mirgh et al 2021 ; Miyashita et al 2020 ; Péron et al 2021 ; Poli et al 2022 ; Li et al 2020a , b ; Reddy et al 2021 ; Ricoca Peixoto et al 2020 ; Giorgi-Rossi et al 2020; Rugge et al 2020 ; Erdal et al 2021 ; Pérez-Segura et al 2021 ; Serraino et al 2021 ; Shahidsales et al 2021 ; Sorouri et al 2020 ; Stroppa et al 2020 ; Vergara et al 2021 ; Vila-Corcoles et al 2021 ; Zhang et al 2021 ; Zhou et al 2021 ) were included in the analysis to compare the mortality rates of cancer and non-cancer patients infected with SARS-CoV-2. There were a total of 557,053 participants, of whom 21,599 were cancer patients.…”
Section: Resultsmentioning
confidence: 99%
“…From a historical cohort study of hospitalized COVID-19 patients in our hospital, we identified patients discharged home, between March 8 and June 14, 2020 [ 5 ]. COVID-19 was confirmed via reverse transcriptase-polymerase chain reaction assay of a nasopharyngeal swab.…”
Section: To the Editormentioning
confidence: 99%